Salinity Variation of Euphrates River between Ashshinnafiyah and Assamawa Cities (Journal of Engineering, 2013)
AshShinnafiyah and AsSamawa cities suffer from significant increase in salinity of Euphrates River water compared with their counterpart's north AshShinnafiyah city which is reflected adversely on the quality of water within the study area. The study aims to find possible solutions to avoid the deterioration of Euphrates River northern AshShinnafiyah city until AsSamawa city that were presented by total dissolved solid TDS. Twelve main hydrological and fifteen salinity measurement stations were selected to cover 117 km of the river reach within the study area during July-2011. Additional twenty three hydrological and salinity stations were adopted during March-2012, winter season to the river within the study area. After conducting the field and laboratory measurements, mathematical model using HEC-RAS v.4.1 software were implemented, using the available geometric and recorded and measured hydrological data. Eleven scenarios were adopted, by canceled one or more of the drains that cause the deterioration in the river, to find the best scenario using various discharges of Al Ya’uo Regulator (Upstream of study area), where the criteria are the water level at AsSamawa city (downstream boundary) is not less than 6 m.a.m.s.l. and the maximum acceptable salinity for agricultural purposes is 1500 mg/l according to Specification of Iraq No. 417 for maintenance of river pollution, 1967. It was concluded from both models that the problem of salinity in the study area cannot be avoided without diverting one or more of the drains that outfall in the river. The minimum instream flow MIF was found for each scenario. Euphrates River without Eastern Al-Jarah, Al-Khassf, AnNagara, and Al-Haffar Drains, and outfalls Between AshShinnafiyah and Garrb Villages, Scenario 9, is the best one, where it gave the minimum required discharge from Al-Ya’uo Regulator of 82m 3 /s and 165m 3 /s during summer and winter seasons respectively.